Pathogenic mechanisms and therapeutic advances of small colony variants - LIANG Xiaoning; SHI Tingwang; CHEN Yunfeng (Shanghai Jiaotong Daxue xuebao. Yixue ban)
Small colony variants (SCVs) are unique phenotypic variants produced by bacteria such as Staphylococcus aureus under environmental selective pressure, with specific biological characteristics, including slow growth, reduced pigment synthesis, auxotrophy, enhanced drug resistance, and easier intracellular colonization and biofilm formation. In recent years, it has been increasingly recognized that SCVs play a crucial role in the chronic progression of infections and poor prognosis. SCVs exhibit significant heterogeneity with complex and diverse molecular profiles. Compared with wild-type strains, SCVs have low virulence and significantly enhanced adherence, and they can effectively evade immune system recognition and clearance. SCVs invade host cells, including macrophages, and form dormant intracellular forms, causing antimicrobial resistance. These variants can revert to wild-type bacteria when environmental conditions improve, causing persistent and refractory infections such as osteomyelitis, cystic fibrosis, and implant-associated infections. However, current treatments for SCV-related infections are limited to long-term antibiotic therapy combined with debridement of infected tissue, and understanding of SCVs, their pathogenic mechanisms, and treatments remains limited. Traditional therapies, such as rifampicin combined with vancomycin, have limited efficacy against intracellular SCVs. Novel strategies, such as targeting ATP synthase inhibitors (eg. lycopene), using nanocarrier-delivered antibiotics to enhance intracellular penetration, alkalinizing of the microenvironment, or disrupting biofilms by physical therapies, are important breakthroughs in the fight against SCV-associated infections. This paper summarizes the biological characteristics, pathogenic mechanisms, and therapeutic progress of SCVs, providing reference for research and treatment of SCV-related infections.